2007
DOI: 10.1080/02841860600902197
|View full text |Cite
|
Sign up to set email alerts
|

CYP450 polymorphisms predict clinic outcomes to vinorelbine-based chemotherapy in patients with non-small-cell lung cancer

Abstract: (2007) CYP450 polymorphisms predict clinic outcomes to vinorelbine-based chemotherapy in patients with non-small-cell lung cancer, Acta Oncologica, 46:3, 361-366,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Consistent with the results of our study, clinical data from Wong et al (2006) support a lack of CYP3A5 contribution to clearance of vinorelbine. In contrast, CYP3A5*1 genotype has even been shown to be moderately associated with better overall median survival rates in patients with NSCLC (Pan et al, 2007). In the study of P450 genotypes and clinical outcomes in patients with NSCLC, they found that patients with at least one CYP3A5*1 allele had slower rates of tumor growth and a higher associated median survival rate than did patients without a CYP3A5*1 allele.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Consistent with the results of our study, clinical data from Wong et al (2006) support a lack of CYP3A5 contribution to clearance of vinorelbine. In contrast, CYP3A5*1 genotype has even been shown to be moderately associated with better overall median survival rates in patients with NSCLC (Pan et al, 2007). In the study of P450 genotypes and clinical outcomes in patients with NSCLC, they found that patients with at least one CYP3A5*1 allele had slower rates of tumor growth and a higher associated median survival rate than did patients without a CYP3A5*1 allele.…”
Section: Downloaded Frommentioning
confidence: 96%
“…For example, patient genotype for various drug metabolism pathways could alter both drug efficacy and drug toxicity. We will not discuss these further in this paper, but several examples of these have been described in lung cancer patients3941. However, we will discuss in later sections how host genotype for specific resistance factors impacts therapy outcome, and examples are presented in Table 2.…”
Section: 0 Backgroundmentioning
confidence: 99%
“…Metagenes MAGEA9B and MAGEA10 have been involved in congenital dyskeratosis,33 and NLRP2 may be involved in another type of familial imprinting disorder 34 . CYP3A5 , located in the second top metagene, contains one of the most commonly detected polymorphisms that influences the efficacy of vinorelbine-based therapies to treat NSCLC 35.…”
Section: Resultsmentioning
confidence: 99%